Fresh Fruit Bunches Forecasting with the Double Exponential Smoothing Method - Anggraini, Yuli; Manurung, Nuriadi; Yuma, Febby Madona (Indonesian Journal of Artificial Intelligence and Data Mining, 2025)
PTPN IV Regional 1 Huta Padang Plantation is an oil palm plantation unit in North Sumatra that manages the cultivation, harvesting, and processing of Fresh Fruit Bunches (FFB) to produce palm oil. During the harvest process to produce Crude Palm Oil (CPO), a lot is often wasted due to unstable market demand. This research aims to implement the double exponential smoothing method for the production of fresh fruit bunches to be used as CPO. The problem faced is that production uncertainty often causes an imbalance between crop yields and market demand. If production is excessive, the company risks a spike in storage costs and potential product spoilage. Conversely, if production is too low, the company may miss out on market opportunities. This forecasting uses historical data from the previous year. The results of research at PTPN IV Regional 1 Kebun Huta Padang show that palm oil production forecasting for February 2025 amounted to 982.97 Kg with an error rate of 7.44%. This value is obtained using an alpha constant of 0.8 which gives the smallest forecasting error rate.